Cannabis use disorder contributes to cognitive dysfunction in Veterans with traumatic brain injury - Esmaeili, Aryan; Dismuke-Greer, Clara; Pogoda, Terri K.; Amuan, Megan E.; Garcia, Carla; Del Negro, Ariana; Myers, Maddy; Kennedy, Eamonn; Cifu, David; Pugh, Mary Jo (Frontiers in Neurology, 2024)
Background: While emerging evidence supports a link between traumatic brain injury (TBI) and progressive cognitive dysfunction in Veterans, there is insufficient information on the impact of cannabis use disorder (CUD) on long-term cognitive disorders. This study aimed to examine the incidences of cognitive disorders in Veterans with TBI and CUD and to evaluate their relationship.Methods: This retrospective cohort study used the US Department of Veterans Affairs and Department of Defense administrative data from the Long-term Impact of Military-Relevant Brain Injury Consortium-Chronic Effects of Neurotrauma Consortium Phenotype study. Diagnoses suggesting cognitive disorders after a TBI index date were identified using inpatient and outpatient data from 2003-2022. We compared the differential cognitive disorders incidence in Veterans who had the following: 1) no CUD or TBI (control group), 2) CUD only, 3) TBI only, and 4) comorbid CUD+TBI. Kaplan-Meier analyses were used to estimate the overall cognitive disorders incidence in the above study groups. The crude and adjusted Cox proportional hazards models were used to estimate crude and adjusted hazard ratios (HRs) for cognitive disorders.Results: A total of 1,560,556 Veterans (82.32% male, median [IQR] age at the time of TBI, 34.51 [11.29] years, and 61.35% white) were evaluated. The cognitive disorder incidence rates were estimated as 0.68 (95% CI, 0.62, 0.75) for CUD only and 1.03 (95% CI, 1.00, 1.06) for TBI only per 10,000 person-months of observations, with the highest estimated cognitive disorder incidence observed in participants with both TBI and CUD (1.83 (95% CI, 1.72, 1.95)). Relative to the control group, the highest hazard of cognitive disorders was observed in Veterans with CUD+TBI (hazard ratio [HR], 3.26; 95% CI, 2.91, 3.65), followed by those with TBI only (2.32; 95 CI%, 2.13, 2.53) and with CUD (1.79; 95 CI%, 1.60, 2.00). Of note, in the CUD only subgroup, we also observed the highest risk of an early onset cognitive disorder other than Alzheimer's disease and Frontotemporal dementia.The results of this analysis suggest that individuals with comorbid TBI and CUD may be at increased risk for early onset cognitive disorders, including dementia.